Taming the mandarin: Some reflections on the looming administrative reforms in Japan - Fajonyomi, S. Banji (1997)
Giving fast erosion of Japanese bureaucracy's prestige in the eyes of its citizens and the likely focus of impending administrative reforms to cover bureaucratic attitude also as the context, the author identifies and discusses some major reforms issues having a bearing on Japanese bureaucracy's behavioural aspects, such as excessive loyalty to their own department, sectionalism in recruitment and career pattern, resistance to change, predominance in the functioning of government and the need to gear its role to Japan's future needs. For readers' benefit, he also provides additional inputs on selectively relevant conceptual framework of his study, instances of recent bureaucratic failures in Japan, mode of institutionalisation of bureaucracy in Japan with its characteristic features (i.e., elitism and its small size), and a brief resume on administrative reforms adopted earlier. - Reproduced
Keywords: Administrative reform - Japan; Administrative reform